2018
DOI: 10.5194/acp-18-259-2018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of global observations and trends of total precipitable water derived from microwave radiometers and COSMIC radio occultation from 2006 to 2013

Abstract: Abstract. We compare atmospheric total precipitable water (TPW) derived from the SSM/I (Special Sensor Microwave Imager) and SSMIS (Special Sensor Microwave Imager/Sounder) radiometers and WindSat to collocated TPW estimates derived from COSMIC (Constellation System for Meteorology, Ionosphere, and Climate) radio occultation (RO) under clear and cloudy conditions over the oceans from June 2006 to December 2013. Results show that the mean microwave (MW) radiometer -COSMIC TPW differences range from 0.06 to 0.18… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 62 publications
3
32
0
Order By: Relevance
“…Being an active limb-sounding measurement, GPS RO technique is capable of retrieving profiles of microwave refractivity at very high vertical resolution [23]. The root mean square (RMS) error was estimated to be less than 1 K based on a detailed theoretical study [23], and this estimate was found to be consistent with numerous cross-validation studies between RO, radiosonde observation (RAOB), and other satellite measurements (e.g., [20,21,[24][25][26][27][28]).…”
Section: Cosmic Temperature and Water Vapor Retrievalssupporting
confidence: 62%
“…Being an active limb-sounding measurement, GPS RO technique is capable of retrieving profiles of microwave refractivity at very high vertical resolution [23]. The root mean square (RMS) error was estimated to be less than 1 K based on a detailed theoretical study [23], and this estimate was found to be consistent with numerous cross-validation studies between RO, radiosonde observation (RAOB), and other satellite measurements (e.g., [20,21,[24][25][26][27][28]).…”
Section: Cosmic Temperature and Water Vapor Retrievalssupporting
confidence: 62%
“…In fact, the study period extends along 19 years (from 2000 to 2018), using one of the longest remote sensing derived climate data sets in the region, with the advantage of covering a wide area that is also considered one of the regions in the world most sensitive to climate change. Other authors have used shorter time series to evaluate AOD and PWV trends [26,27]. It is also the first study to apply a new methodology (which has been successfully tested on nine specific stations previously [23]) to a wide area, taking advantage of the extensive coverage provided by satellites.…”
Section: Introductionmentioning
confidence: 99%
“…While microwave imagers can provide data under cloudy conditions, they can only retrieve accurate data over ocean due to the complexity of land surface emissivity. And for the GPS‐RO data, although it has all weather observations both over land and ocean, its horizontal resolution is very coarse, which is about 200 km (Ho et al, ; Teng et al, ). Actually, no single sensing technique can completely provide homogeneous data products across the whole globe and under all weather conditions with high frequency and accuracy (Ho et al, ; Ho & Peng, ).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies also show that sampling errors may cause the estimates of climate variables to be uncertain. For example, Ho et al () validated the accuracy of Constellation System for Meteorology, Ionosphere, and Climate (COSMIC) data with collocated microwave radiometer measurements. But finally, a much higher global TPW trend was got with this validated data set.…”
Section: Introductionmentioning
confidence: 99%